2004
DOI: 10.1158/1078-0432.ccr-03-0631
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Surgical Margins and Local Recurrence in Head and Neck Cancer Patients

Abstract: Purpose: Approximately 10 -30% of surgically treated head and neck cancer patients develop local recurrences while the resection margins are histologically tumor free. These recurrences may arise from cancer cells left behind but not detected by the pathologist, or they may develop from precursor lesions adjacent to the tumor that were not completely resected. We have investigated whether TP53-mutated DNA in the surgical margins is suitable to identify patients with head and neck squamous cell carcinoma at ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
134
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(139 citation statements)
references
References 10 publications
4
134
0
1
Order By: Relevance
“…Earlier studies have shown that p53 overexpression screened by the same antibody used in the current study to evaluate positive tumour margins could be used to predict local recurrence. This study additionally showed that a small cluster of p53-positive carcinoma cells could be observed that was already present in the routine H&E staining but was missed by routine histology (Houten et al, 2004).…”
Section: Discussionsupporting
confidence: 51%
“…Earlier studies have shown that p53 overexpression screened by the same antibody used in the current study to evaluate positive tumour margins could be used to predict local recurrence. This study additionally showed that a small cluster of p53-positive carcinoma cells could be observed that was already present in the routine H&E staining but was missed by routine histology (Houten et al, 2004).…”
Section: Discussionsupporting
confidence: 51%
“…Second, it might be difficult to determine the margins of lesions during procedures. Moreover, genetically altered cells have been found to extend into clinically and histologically 'normal' regions (van Houten et al, 2004;Poh et al, 2006). Third, histopathology requires time for processing.…”
mentioning
confidence: 99%
“…One study has reported that eIF4E overexpression found in cancer tissue than the normal mucosa by using IHC (Rosenwald et al, 2001). Association between p53 and eIF4E expression and clinical outcomes A previous study suggests that IHC staining with p53 has an advantage over histopathology to identify the patients at high risk for local recurrence (Van Houten et al, 2004). This finding indicate some limitations of histological diagnosis and the potential for molecular markers to guide clinicians in the management of HNSCC (Nathan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, five year survival rate in HNSCC is lower than other cancers, such as those of colorectal, cervix, and breast origin, due to detection of advanced stage disease (Jemal et al, 2008;Clark et al, 2010). With advent of new surgical procedures, improved radiotherapy and concomitant chemotherapy, there is a considerable improvement in local recurrence (Van Houten et al, 2004). However, the survival rates for HNSCC have not significantly improved (Partridge et al, 2007;Argiris et al, 2008).…”
Section: Introductionmentioning
confidence: 99%